Monoaminergic impairment in Down syndrome with Alzheimer's disease compared to early‐onset Alzheimer's disease. Issue 1 (23rd November 2017) - Dekker, Alain D.; Vermeiren, Yannick; Carmona‐Iragui, Maria; Benejam, Bessy; Videla, Laura; Gelpi, Ellen; Aerts, Tony; Van Dam, Debby; Fernández, Susana; Lleó, Alberto; Videla, Sebastian; Sieben, Anne; et al.
Abstract: Introduction: People with Down syndrome (DS) are at high risk for Alzheimer's disease (AD). Defects in monoamine neurotransmitter systems are implicated in DS and AD but have not been comprehensively studied in DS. Methods: Noradrenaline, adrenaline, and their metabolite 3‐methoxy‐4‐hydroxyphenylglycol (MHPG); dopamine and its metabolites 3, 4‐dihydroxyphenylacetic acid (DOPAC) and homovanillic acid; and serotonin and its metabolite 5‐hydroxyindoleacetic acid were quantified in 15 brain regions of DS without AD (DS, n = 4), DS with AD (DS+AD, n = 17), early‐onset AD (EOAD, n = 11) patients, and healthy non‐DS controls (n = 10) in the general population. Moreover, monoaminergic concentrations were determined in cerebrospinal fluid (CSF)/plasma samples of DS (n = 37/149), DS with prodromal AD (DS+pAD, n = 13/36), and DS+AD (n = 18/40). Results: In brain, noradrenergic and serotonergic compounds were overall reduced in DS+AD versus EOAD, while the dopaminergic system showed a bidirectional change. For DS versus non‐DS controls, significantly decreased MHPG levels were noted in various brain regions, though to a lesser extent than for DS+AD versus EOAD. Apart from DOPAC, CSF/plasma concentrations were not altered between groups. Discussion: Monoamine neurotransmitters and metabolites were evidently impacted in DS, DS+AD, and EOAD. DS and DS+AD presented a remarkably similar monoaminergic profile, possibly related to early deposition of amyloid pathology in DS. To confirm whether monoaminergic alterations are indeed due to early amyloid β accumulation, future avenues include positron emission tomography studies of monoaminergic neurotransmission in relation to amyloid deposition, as well as relating monoaminergic concentrations to CSF/plasma levels of amyloid β and tau within individuals. Highlights: Monoaminergic changes are found in Alzheimer's disease (AD) and Down syndrome (DS). We characterized 15 brain regions of DS, DS+AD, early‐onset AD, and non‐DS controls. Noradrenergic and serotonergic compounds were reduced in DS+AD versus early‐onset AD postmortem brain tissue. DS and DS+AD cases presented rather similar monoaminergic profiles in postmortem brain tissue. Monoaminergic CSF/plasma levels were not related to clinical dementia status in DS.